Digital divide and growth gap: A cumulative relationship - Youngsoo Lee; Jeonghun Oh; Hwanjoo Seo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper, using a cumulative growth model and a catch-up model, verifies the cumulative relationship between IT investment and economic growth, and then examines whether this relationship enlarges the differences in the economic growth among OECD countries. We observe the following results: first, those countries making a rapid progress in IT capital formulation enhance labour productivity faster than the average OECD member countries. Second, non-IT capital has larger impacts on the economy than IT capital. Third, those countries with relatively lower productivity levels can reduce the gap using knowledge spillovers from advanced countries. Fourth, IT investment and expansion increase labour productivity in OECD member countries. Fifth, countries with a solid infrastructure and skilled human resources increase IT investment even more actively. Lastly, the cumulative relationship between IT investment and productivity is shown to be valid and thus this might enlarge the disparity between countries according to the economic possibilities provided by IT investment. – IT ; growth gap ; cumulative relationship
Keywords: O3; O4; E2; 330; Informationstechnik; Investition; Wirtschaftswachstum; Theorie; OECD-Staaten; Digital Divide